The Effectiveness of Robomind Software in Basic Programming Learning. - Maf’ulah, Ismi Amrina; Efendi, Agus; Basori, Basori (Universitas Sebelas Maret, 2017)
This research aim to find out: (1) the differences of cognitive abilities of students who learn using media software RoboMind and students who learn without using media software RoboMind in learning basic programming, (2) the used of media software RoboMind in learning basic programming is more effective than without used media software RoboMind to improve cognitive ability of first grade students. This research used quasi experimental approach with Pretest Posttest Control Group Design. This research was conducted at SMK Negeri 7 Surakarta. The population of this research were all students of first grade students in Multimedia Study Program at SMK N 7 Surakarta. Based on the result of this research can be concluded that: (1) there was difference of cognitive abilities of students who learn using media software RoboMind and students who learn without used media software in learning basic programming (tcount: 2,085 > ttable: 1,99962). (2) the use of media software RoboMind in learning basic programming is more effective than without used media software RoboMind to improve cognitive ability of first grade students at SMK Negeri 7 Surakarta (tcount: 3,517 > ttable: 1,99962). This work is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.